Associations between family ratings on experience with care and clinical quality-of-care measures for nursing home residents - Li, Yue (Med Care Res Rev, 2015)
Several states are currently collecting and publicly reporting nursing home resident and/or family member ratings of experience with care in an attempt to improve person-centered care in nursing homes. Using the 2008 Maryland nursing home family survey reports and other data, this study performed both facility- and resident-level analyses, and estimated the relationships between family ratings of care and several long-term care quality measures (pressure ulcers, overall and potentially-avoidable hospitalizations, and mortality) after adjustment for resident characteristics. We found that better family evaluations of overall and specific aspects of care may be associated with reduced rates of risk-adjusted measures at the facility level (range of correlation coefficients: −0.01 to −0.31). Associations of overall experience ratings tended to persist after further adjustment for common nursing home characteristics such as nurse staffing levels. We conclude that family ratings of nursing home care complement other types of performance measures such as risk-adjusted outcomes.